Treatment of smouldering coal refuse piles: an application in China. Issue 23 (14th October 2020) - Shao, Zhenlu; Wang, Deming; Cao, Kai; Si, Weibin; Li, Yizhou; Liu, Jiaolong
ABSTRACT : Coal refuse pile fires are a serious health, safety, and environment hazard. The fires in Guoshan Coal Refuse Pile affect daily life of the local residents. Although conventional fire control methods (water injection, grouting and surface sealing) were used to control the fires, they rekindled soon after the fire-fighting engineering was quitted. Thus, effective methods need to be applied to extinguish the fires completely without reignition. In this paper, the environmental impact of the fire on the local land, water and air is illustrated by sample analysis and photos. The self-potential method, which achieves remote detection from the ground surface, is adopted to delineate the scope of the fires to give support for the efficient and economical extinguishment of them. The three-phase foam containing water, gas and loess is proposed to control and extinguish the fires. The corresponding fire-fighting system is also invented to fit the field work and put out the fires more efficiently and conveniently. The temperature monitoring result shows that the fires are extinguished successfully with no sign of reignition. GRAPHICAL ABSTRACT: UF0001